2006
DOI: 10.1007/bf03022502
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia and Pain Targeted thoracic epidural blood patch placed under electrical stimulation guidance (Tsui test)

Abstract: Purpose: This case report describes the use of electrical epidural stimulation (Tsui test) to confirm accurate placement of a thoracic epidural catheter when administering an epidural blood patch for headache management in a patient suffering from spontaneous intracranial hypotension. Clinical features:A 41-yr-old female presented to the Chronic Pain Clinic with a history of postural headache symptoms worsening in severity over several years. Two previous blood patches performed at T11-12 and T10-11 respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] The motor threshold current (MTC) achieved when using the EST can distinguish whether the catheter tip is positioned epidurally (medium MTC: 2-15 mA), subcutaneously (high MTC: [ 15 mA), or intrathecally (low MTC: \ 2 mA), although a low MTC might also conceivably be due to the catheter abutting a nerve root. It should be emphasized that these MTC ranges are somewhat arbitrary depending on the individual interpreting the EST results.…”
Section: Résumémentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] The motor threshold current (MTC) achieved when using the EST can distinguish whether the catheter tip is positioned epidurally (medium MTC: 2-15 mA), subcutaneously (high MTC: [ 15 mA), or intrathecally (low MTC: \ 2 mA), although a low MTC might also conceivably be due to the catheter abutting a nerve root. It should be emphasized that these MTC ranges are somewhat arbitrary depending on the individual interpreting the EST results.…”
Section: Résumémentioning
confidence: 99%
“…We herein report the successful treatment of SIH with a neurostimulation-guided cervical epidural blood patch using the electrical epidural stimulation Tsui test. 2 A 48-yr-old woman presented to our neurosurgery department with a five-month history of a left occipital headache and episodes of aphasia. Magnetic resonance imaging (MRI) showed a 13-mm frontoparietal subdural hematoma with evidence of subacute-on-chronic hemorrhage and dural enhancement throughout ( Figure A).…”
Section: To the Editormentioning
confidence: 99%
“…We appreciated the case report by Morley-Forster et al demonstrating the elegant utility of the Tsui test for the precise placement of a thoracic epidural blood patch. 1 However, we are troubled by the unwarranted (in our opinion) caution the authors used to initiate their epidural entry at T 6-7 rather than begin at the T2-4 level where the indium cerebrospinal fluid flow (CSF) flow study demonstrated the CSF leak. Their stated reason for avoiding the T2-4 interspace was based on "a recent study (that) showed that the cervical and upper thoracic ligamentum flavum above T4 frequently fails to fuse in the midline."…”
Section: Risks Of Dural Puncture Associated With Thoracic Epiduralsmentioning
confidence: 99%
“…We appreciate the interest shown by Drs. Beriault and Korzeniewski in our recent case report 1 describing the use of the Tsui test to target placement of a thoracic epidural blood patch. These authors object to our expressed caution in entering the epidural space between T2 and T4, based on both their own extensive experience with high thoracic epidural placement, and their concern that the cited findings of failure of ligamentum flavum fusion in the midline reported by Lirk et al, 2 Although we agree that, in experienced hands, epidural catheter placement at the T2-4 level is generally safe, not all anesthesiologists share this level of experience and confidence with the anatomy.…”
Section: Replymentioning
confidence: 99%